A dynamic model of electronic wedge brake: experimental, control and optimization - Che Hasan, Mohd Hanif; Hassan, Mohd Khair; Ahmad, Fauzi; Marhaban, Mohammad Hamiruce; Haris, Sharil Izwan (Institute of Advanced Engineering and Science (IAES), 2021)
This paper discusses the process of modelling and parameter selection for the creation of the electronic wedge brake system (EWB). The system involves a permanent magnet DC engine (PMDC) that drives the motor, the gear leadscrew and the brake core. The proposed model is simpler and more flexible which can be used in both the most well-known EWB designs either natural or optimized EWB. The selection of the motor is rendered according to the brake specifications. The wedge angle profile is centred on the derivation of EWB system that consists of brake actuator, wedge mechanism dynamic and wedge characteristic brake factor. Control and optimization are carried out with specific coefficients of friction of the brake pads to maintain operating reliability. A 5th-order brake simulation model of the EWB in a single state-space was derived and a simulation was conducted to verify the distribution of force. The efficiency of the brake clamping force control system was assessed by proportional-integral-derivative (PID) control. The performance of the proposed controller is verified in simulations and experiments using a prototype electronic wedge brake. The research findings indicate, the actuator restriction is deemed to achieve consistent performance against full range braking during the EWB control design.